Intimate partner violence and breastfeeding practices in South Africa - Lemao, Moipone (My University, 2020)
Background: Breastfeeding is the best source of food for infants because it is uncontaminated and contains all nutrients necessary for them in the first months of life. As such, World Health Organisation recommends that infants should receive breast milk exclusively for the first six months of life. As of 2016, the exclusive breastfeeding rates were 32%, while the proportion of bottle-feeding was 45% in South Africa. Despite all efforts to promote and support breastfeeding in South Africa, women still encounter challenges that prevent them from exclusively breastfeeding. Further, women with a history of Intimate Partner Violence are at high risk of known reproductive and other health problems and it could also be one of the reasons for low rates of exclusive breastfeeding. While the impact of IPV on breastfeeding has been acknowledged in the literatures, there is noticeable lack of empirical information on the relationship between physical IPV and breastfeeding, especially in South Africa. The purpose of the study is to examine the relationship between IPV and breastfeeding practices in South Africa. Methods: The study used the South African Demographic and Health Survey data set of 2016. The study population was women of reproductive ages (15-49) who had a child in the last six months before the survey, and who participated in the domestic violence module. Percentage and frequency distributions and cross-tabulations were used to describe breastfeeding practices and the independent variables in the study. The association between breastfeeding practices and the independent variables were determined using multinomial logistic regression. Results: Findings from this study indicated that the larger proportion of women were not breastfeeding while only 10% were exclusively breastfeeding. In crude multinomial logistic regression analysis, women who experienced physical IPV were more likely to exclusively breastfeed compared to their counterparts. The study also revealed that physical IPV was associated with lower odds of no breastfeeding (RRR 0.394, p = 0.025). In analysis adjusted for socio-economic, contextual and partner variables, physical IPV was associated with higher odds of exclusive breastfeeding. However, rates of no breastfeeding were not statistically different between women who experienced physical IPV and those who did not experience physical IPV (aRRR0.44, p = 0.103). Conclusions: The study found that physical IPV was positively associated with exclusive breastfeeding. Thus, more efforts are needed to scale-up rates of exclusive breastfeeding among all women and fight against physical IPV as it can have long term consequences on the health of the mother and the child and affect human rights
A research report submitted to the Faculty of Humanities, School of Public Health and Social Sciences, University of Witwatersrand, in partial fulfilment of the requirements of Master of Arts in the field of Demography and Population Studies, 2020